How cultural similarities can lead to cultural difficulties - Smit, Chris (Henry Stewart Talks, 2019)
Cooperation between cultures following the same trend, Similarity in a cultural profile, Similarity doesn’t guarantee smooth cooperation, How to make use of existing cultural similarities, Practical tips to facilitate cultural integration and effectiveness